As políticas do estado e a indústria de bens de capital: os impactos no emprego e na estrutura produtiva nacional da indústria parapetrolífera no período de 2003 a 2013 - Cardoso, Andre De Oliveira [UNIFESP] (2019)
The objective of this dissertation is to analyze the policies of the Brazilian State from 2003 to 2013 for the capital goods industry and the impact of these policies on the employment and productive structure of the the parapetrolifer industry (IPP). It sought to analyze the existence of the relationship of the country's economic development and the growth of its industry as a result of the intentional measures of the Brazilian government. The method used was based on the historical analysis of the Brazilian reality in the capitalist system from the development and underdevelopment theories, from the analysis of the public policies of the Brazilian State for the capital goods and parapetrolifer industry and, finally, proceeded to the empirical analysis of the sector, with the construction of economic indicators that made it possible to capture the transformations studied in the IPP, the main indicators related to employment are employment growth rate, global and discounted turnover rate, growth rate of average remuneration, workers' education index and overall productivity and production. The main indicators related to the productive structure are the growth rate of companies, production density, investment rate, export coefficient, import coefficient and import penetration coefficient. The analysis showed that the policies of the Brazilian State for IPP, although they have presented positive results for the labor market, with the expansion of jobs, income and qualification, did not have any impact on the transformation of the national productive structure, with the specialization of the national parapetroliferous industry in the products with lower added value.